Trends of children's height and parental unemployment: a large-scale anthropometric study on Eastern Germany, 1994 - 2006 - Jörg Baten; Andreas Böhm (Center for Economic Studies and ifo Institute (CESifo), 2008)
The average height of children is an indicator for the quality of nutrition and health care. Heights have never declined over longer time spans in Eastern Germany since 1880 - except for the most recent period 1997-2006. In the Eastern German Land of Brandenburg, a data set of 253,050 pre-school height measurements was compiled and complemented with information on parents' schooling and employment status. Unemployment might have negative psychological effects, with impact on health care. Both a panel analysis of districts and an assessment at the individual level yield the result that increasing unemployment was in fact the major driving force.
Keywords: E24; H53; I12; I32; 330; height; unemployment; Eastern Germany; welfare measurement; Gesundheit; Kinder; Arbeitslosigkeit; Eltern; Wohlfahrtseffekt; Brandenburg; Neue Bundesländer; Deutschland